IAIN Curup's Public Relations Strategy in Branding the Campus Through the Use of Social Media in New Student Admission Promotion - Ibnu Amin; Hendri Saputra (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to explore the communication strategies of IAIN Curup’s Public Relations (PR) in branding the campus through the utilization of social media for the promotion of new student admissions. Every academic year, higher education institutions face the challenge of declining numbers of prospective new students, which becomes a seasonal concern. This research employs a qualitative descriptive approach with a field research method to uncover the underlying phenomena related to the promotional strategies. Informants were selected using purposive sampling to obtain maximal data. The results indicate that the role of the PR department in higher education is highly strategic in ensuring the dissemination of information regarding the institution's vision, mission, and leadership policies to the public, as part of institutional branding. The task of PR is to create a positive perception in the community about the campus through various branding attributes. Furthermore, from 2019 to 2022, IAIN Curup’s PR utilized seven social media platforms for campus branding, including Facebook, Instagram, Twitter (X), YouTube, and TikTok. The use of these social media platforms successfully reached thousands of followers and visitors. Additionally, the branding strategy was realized through planning, implementation, and evaluation to enhance the effectiveness of new student admission promotions.